2021
DOI: 10.1590/1984-0462/2021/39/2020005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postural Education in Elementary School Children: A Systematic Review

Abstract: Objective: To determine the effect of postural education on the learning and postural habits of elementary school children without physical intervention. Methods: We searched PubMed, Lilacs, SciELO, Cochrane, and Science Direct data bases and reference lists of studies in February 2020. The eligibility criteria were randomized clinical trials related to the effect of postural education in children aged between 6 and 12 years old. Two authors independently assessed trials for inclusion and risk of bias: rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In this sense, schools play an important role. There have been certain interventions with diverse components that were assessed in randomized trials as possible choices for teaching postural education to elementary school children, with various components adapted to the children’s age range [ 38 ]. Once the postural education sessions had been analyzed, all the proposals were adapted to the child population, including active methodology, comic books, games, and characters, among other things, and focused on biomechanics, the spinal column, and posture.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, schools play an important role. There have been certain interventions with diverse components that were assessed in randomized trials as possible choices for teaching postural education to elementary school children, with various components adapted to the children’s age range [ 38 ]. Once the postural education sessions had been analyzed, all the proposals were adapted to the child population, including active methodology, comic books, games, and characters, among other things, and focused on biomechanics, the spinal column, and posture.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the intervention programs’ duration, the present study proposed a 5-week intervention with sessions of 3 days a week (2 hours per session). According to what has been published by other authors, the duration of the reported interventions differs from ours, with interventions of six 60-minute sessions, 18,29 6 weeks, 30 9 weeks once a week with a duration of one and a half hours. 25 Studies in which the duration of the intervention was 1 week, from 2 to 6 weeks, from 8 to 15 weeks and even 96 weeks 25,27,31-35 which proves its effectiveness and usefulness in a few weeks but with greater hourly intensity.…”
Section: Discussionmentioning
confidence: 47%
“…At the moment, the results on the positive effects as to acquiring knowledge and postural habits found in the studies are inconclusive [12]. The hypothesis of the present study is that postural education will improve the children's postural habits, and that these improved postural habits will result in a lower prevalence of LBP, preventing its onset at an early age and reducing the intensity and frequency of pain in those cases where LBP is already present.…”
Section: Introductionmentioning
confidence: 71%
“…However, it is currently di cult to carry out a face-to-face intervention in schools, due to the COVID-19 pandemic. While it is certain that other studies on habit change have been carried out telematically (mHealth interventions) [10,11], to the best of our knowledge, none have been carried out in child population [12], due to the complexity involved in interventions with children, such as the limited use of personal mobile phones, or the need to involve families in the interventions, due to their fundamental role in shaping their children's health choices [13].…”
Section: Introductionmentioning
confidence: 99%